2019
DOI: 10.1111/anae.14669
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fresh gas flow during induction of anaesthesia on sevoflurane usage: a quality improvement study

Abstract: Reducing fresh gas flow during inhalational anaesthesia results in cost savings and decreases environmental impact. We are interested in the influence of fresh gas flow on the early (induction) phase of overall fresh gas flow and vapour consumption. This stage is often excluded in studies of fresh gas flow. Data were collected from 3199 sevoflurane anaesthetics over an 11-month period in four operating theatres. We determined fresh gas flow at different stages of anaesthesia, and developed an explanatory model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The role of high FGF during the wash‐in period on consumption has not been studied much. In a current study, Kennedy et al 14 collected data from 3199 sevoflurane anesthetics and investigated the impact of FGF in the wash‐in period of anesthesia on the volatile agent consumption. They concluded that changing FGF in the early phase can make a large difference on vapor consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The role of high FGF during the wash‐in period on consumption has not been studied much. In a current study, Kennedy et al 14 collected data from 3199 sevoflurane anesthetics and investigated the impact of FGF in the wash‐in period of anesthesia on the volatile agent consumption. They concluded that changing FGF in the early phase can make a large difference on vapor consumption.…”
Section: Discussionmentioning
confidence: 99%
“…We 5 recently demonstrated that the length of time spent at an initial high flow rate is a major contributor to overall vapour consumption and that vapour consumption essentially matches the area under the flow rate/time curve. Based on this work the difference in desflurane consumption between machines is likely due to the higher flow rates seen in the Flow‐i over the first 5‐8 min.…”
mentioning
confidence: 95%
“…Our work suggests that the minimum FGF used during maintenance is only one of many factors contributing to total vapour consumption 5 . We frequently encounter users who claim they have no need for automated systems or to modify their practice stating “I always use a flow rate of 300 ml (or 200 ml).” These individuals are invariably only referring to the middle of the maintenance phase and such claims need to be met with request for actual data, such as that provided by Mostad et al Our data suggests that, broadly speaking, the minimum FGF used during maintenance is a relatively unimportant factor in reducing total vapour consumption.…”
mentioning
confidence: 99%
“…The environmental impacts of inhaled anaesthetic agents are well described [1]. Our group has a long interest in reducing fresh gas flow (FGF) rates to reduce economic and environmental costs associated with volatile anaesthesia [2].…”
mentioning
confidence: 99%